両方とも前のリビジョン前のリビジョン次のリビジョン | 前のリビジョン |
softwares:root:convolution_by_gaussian [2018/02/21 00:09] – [Notes] kobayash | softwares:root:convolution_by_gaussian [2018/06/16 13:50] (現在) – kobayash |
---|
| |
==== Convoluting TTree's value ==== | ==== Convoluting TTree's value ==== |
* In order to convolute the TTree's value by TTree::Draw(), type in the following command. <code> | * In order to convolute the TTree's value by TTree::Draw(), type the following command. <code> |
tree->Draw("mean+sigma*sqrt(2)*TMath::ErfInverse(2*rndm-1)") | tree->Draw("mean+sigma*sqrt(2)*TMath::ErfInverse(2*rndm-1)") |
</code> For instance, if we want to convolute an energy spectrum with energy resolution $\sigma(E) = 0.01\sqrt{E}$, type in the command as below.<code> | </code> For instance, if we want to convolute an energy spectrum with energy resolution $\sigma(E) = 0.01\sqrt{E}$, type the following command.<code> |
tree->Draw("E+0.01*sqrt(E)*sqrt(2)*TMath::ErfInverse(2*rndm-1)") | tree->Draw("E+0.01*sqrt(E)*sqrt(2)*TMath::ErfInverse(2*rndm-1)") |
</code> In this command, E is a branch or leaf of the energy variable. | </code> In this command, E is a branch or leaf of the energy variable. |
* Derivation of the formula "mean+sigma*sqrt(2)*TMath::ErfInverse(2*rndm-1)" | * Derivation of the formula "mean+sigma*sqrt(2)*TMath::ErfInverse(2*rndm-1)" |
* In general, if we want to shoot random numbers filling in a normalized probability distribution $P(y)$, the random numbers $y$ can be calculated by the inverse function of integral of the $P(y)$, $F^{-1}(x)$, where $F(x)=\int_{-\infty}^x P(t) dt$ and $x$ is an uniform random variable with the range of $0 < x <1$. Therefore, in order to shoot $y$ filling in a normal (Gaussian) distribution $f(x;\mu,\sigma^2) = \frac{1}{\sigma\sqrt{2\pi}}e^{-\frac{(x-\mu)^2}{2\sigma^2}}$, $y$ can be calculated by the inverse function of the integral of the normal distribution, $F^{-1}(x)$. Based on the calculations below, $F^{-1}(x)$ is described as \begin{align} | * In general, if you want to shoot random numbers $y$ filling in a normalized probability distribution $P(y)$, the numbers $y$ can be calculated by the inverse function of integral of the $P(y)$. Now let us define the inverse function of integral of the $P(y)$ as $F^{-1}(x)$, where $F(x)=\int_{-\infty}^x P(t) dt$ and $x$ is an uniform random variable with the range of $0 < x <1$. In order to shoot $y$ filling in a normal (Gaussian) distribution $f(x;\mu,\sigma^2) = \frac{1}{\sigma\sqrt{2\pi}}e^{-\frac{(x-\mu)^2}{2\sigma^2}}$, $y$ can be calculated by the inverse function of the integral of the normal distribution. Based on the following calculations, $F^{-1}(x)$ is described as \begin{align} |
y = F^{-1}(x) = \sqrt{2}\sigma\ \mathrm{erf}^{-1}\left(2x - 1\right) + \mu, | y = F^{-1}(x) = \sqrt{2}\sigma\ \mathrm{erf}^{-1}\left(2x - 1\right) + \mu, |
\end{align} where $ 0 < x < 1$. Fortunately, the ROOT has an implementation of the inverse error function $\mathrm{erf}^{-1}(x)$ ([[https://root.cern.ch/root/html524/TMath.html#TMath:ErfInverse|TMath::ErfInverse()]]), and thus the random numbers filling in the normal distribution $f(x;\mu,\sigma^2)$ can be shot by "mean+sigma*sqrt(2)*TMath::ErfInverse(2*rndm-1)". In the formula, "rndm" is an uniform random number in the range (0,1). | \end{align} where $ 0 < x < 1$. Fortunately, the ROOT has an implementation of the inverse error function $\mathrm{erf}^{-1}(x)$ ([[https://root.cern.ch/root/html524/TMath.html#TMath:ErfInverse|TMath::ErfInverse()]]), and thus the random numbers filling in the normal distribution $f(x;\mu,\sigma^2)$ can be shot by "mean+sigma*sqrt(2)*TMath::ErfInverse(2*rndm-1)". In the formula, "rndm" is an uniform random number in the range (0,1). |
* At first, we have to obtain the integral of the normal (Gaussian) distribution $f(t;\mu,\sigma^2)$, $F(x)$. The integral $F(x)$ can be written as \begin{align} | * At first, we have to obtain the integral $F(x)$ of the normal (Gaussian) distribution $f(t;\mu,\sigma^2)$. $F(x)$ can be written as \begin{align} |
F(x) = \int_{-\infty}^x f(t;\mu,\sigma^2) dt = \frac{1}{2}\left[1+\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right], | F(x) = \int_{-\infty}^x f(t;\mu,\sigma^2) dt = \frac{1}{2}\left[1+\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right], |
\end{align} where $ 0 < F(x) < 1$. The derivation is the following. Assuming $T=\frac{t-\mu}{\sqrt{2}\sigma}$, $\sqrt{2}\sigma dT = dt$, and \begin{align} | \end{align} where $ 0 < F(x) < 1$. The derivation is the following. Assuming $T=\frac{t-\mu}{\sqrt{2}\sigma}$, $\sqrt{2}\sigma dT = dt$, and \begin{align} |
\end{align} Since $\mathrm{erf}(x) = \dfrac{2}{\sqrt{\pi}}\displaystyle\int_0^x e^{-t^2}dt$ and $\mathrm{erf}(-\infty) = \dfrac{2}{\sqrt{\pi}}\displaystyle\int_0^{-\infty} e^{-t^2}dt = -1$, finally we get \begin{align} | \end{align} Since $\mathrm{erf}(x) = \dfrac{2}{\sqrt{\pi}}\displaystyle\int_0^x e^{-t^2}dt$ and $\mathrm{erf}(-\infty) = \dfrac{2}{\sqrt{\pi}}\displaystyle\int_0^{-\infty} e^{-t^2}dt = -1$, finally we get \begin{align} |
F(x) = \frac{1}{2}\left[1+\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right]. | F(x) = \frac{1}{2}\left[1+\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right]. |
\end{align} By the way, $F(x)$ can vary in $ 0 < F(x) < 1$, because $\mathrm{erf}(x)$ can vary in $-1 < \mathrm{erf}(x) < 1$. (In fact, this is trivial, because the $f(x;\mu,\sigma^2)$ is a probability distribution and should be larger than 0. In addition, the integral of the $f(x;\mu,\sigma^2)$ is normalized to 1.) | \end{align} By the way, $F(x)$ can vary in $ 0 < F(x) < 1$, because $\mathrm{erf}(x)$ can vary in $-1 < \mathrm{erf}(x) < 1$. (In fact, this is trivial, because the $f(x;\mu,\sigma^2)$ is a probability distribution and should be larger than $0$. In addition, the integral of the $f(x;\mu,\sigma^2)$ is normalized to $1$.) |
* Then the inverse function of the integral of the normal distribution, $F^{-1}(x)$, can be obtained as below. From $F(x) = \frac{1}{2}\left[1+\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right]$, \begin{align} | * Then the inverse function, $F^{-1}(x)$, of the integral of the normal distribution can be obtained as below. From $F(x) = \frac{1}{2}\left[1+\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right]$, \begin{align} |
\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right) &= 2F(x) - 1\\ | \mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right) &= 2F(x) - 1\\ |
\Rightarrow \mathrm{erf}^{-1}\left[\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right] &= \mathrm{erf}^{-1}\left[2F(x) - 1\right]\\ | \Rightarrow \mathrm{erf}^{-1}\left[\mathrm{erf}\left(\frac{x-\mu}{\sqrt{2}\sigma}\right)\right] &= \mathrm{erf}^{-1}\left[2F(x) - 1\right]\\ |